Method for producing recycled positive electrode active material

JP7631591B1Active Publication Date: 2025-02-18SUMITOMO CHEM CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024054748
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-28
Publication Date
2025-02-18
Estimated Expiration
2044-03-28

Smart Images

  • Figure 0007631591000001_ABST
    Figure 0007631591000001_ABST
Patent Text Reader

Abstract

Components other than the positive electrode active material are efficiently removed from the mixture after heating. [Solution] A method for producing recycled positive electrode active material powder includes (1) a step of mixing an activation treatment agent with a positive electrode composite containing a positive electrode active material powder and a carbon-containing material to obtain a mixture, (2) a step of heating the mixture to obtain a heated mixture containing the heated positive electrode active material powder, and (3) a step of removing components other than the heated positive electrode active material powder from the heated mixture. Step (3) includes a substep of (A1) contacting the heated mixture or the partially removed mixture with a liquid containing water to obtain a slurry S1 containing the heated positive electrode active material powder, (A2) wet classifying the heated positive electrode active material powder in the slurry S1 to obtain a slurry S2 containing the heated positive electrode active material powder having a relatively small average particle size and a slurry S3 containing the heated positive electrode active material powder having a relatively large average particle size, and (A3) a substep of performing solid-liquid separation of the slurry S3.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a recycled positive electrode active material. [Background technology]

[0002] The positive electrode active material of a battery contains rare metal components such as cobalt, nickel, manganese, and lithium, and in particular, the positive electrode active material of a non-aqueous electrolyte secondary battery uses a compound mainly composed of the above rare metal components. In order to conserve the resources of rare metal components, a method for reproducing the rare metal components from waste battery materials of secondary batteries is required.

[0003] For example, Patent Document 1 discloses a method for recovering a positive electrode active material by mixing a positive electrode composite with an activation treatment agent containing an alkali metal compound, heating the mixture to decompose the binder to obtain a heated mixture, adding water to the heated mixture to form a slurry, and then performing solid-liquid separation to recover a positive electrode active material. This method is cost-effective in that it does not use an organic solvent and directly recovers a positive electrode active material from battery waste. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-186150 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in Patent Document 1, there is still room for improvement in terms of efficiently removing components other than the positive electrode active material from the mixture after heating.

[0006] The present invention has been made in consideration of the above problems, and has an object to provide a method for producing a recycled positive electrode active material that can efficiently remove components other than the positive electrode active material from a mixture after heating. [Means for solving the problem]

[0007] [1] (1) A step of mixing a positive electrode mixture containing a positive electrode active material powder and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture; (2) heating the mixture to obtain a heated mixture containing a heated positive electrode active material powder; and (3) A method for producing a recycled positive electrode active material powder, comprising the step of removing components other than the heated positive electrode active material powder from the heated mixture, Step (3) is (A1) a sub-step of contacting the heated mixture or a partially removed mixture in which components other than the heated positive electrode active material powder are partially removed from the heated mixture with a liquid containing water to obtain a slurry S1 containing the heated positive electrode active material powder; (A2) a sub-step of wet-classifying the heated positive electrode active material powder in the slurry S1 to obtain a slurry S2 containing the heated positive electrode active material powder having a relatively small average particle size and a slurry S3 containing the heated positive electrode active material powder having a relatively large average particle size; and (A3) a sub-step of subjecting the slurry S3 to solid-liquid separation.

[0008] [2] The method according to [1], wherein the substep (A1) is a substep of contacting the heated mixture with a liquid containing water to obtain a slurry S1 containing the heated positive electrode active material powder.

[0009] [3] The method according to [1], wherein the substep (A1) is a substep of contacting a liquid containing water with a partially removed mixture in which components other than the heated positive electrode active material powder have been partially removed from the heated mixture, to obtain a slurry S1 containing the heated positive electrode active material powder.

[0010] [4] The method according to [1] or [2], wherein the wet classification in the sub-step (A2) is carried out using a wet sieve or a wet cyclone. Effect of the Invention

[0011] According to the present invention, there is provided a method for producing a recycled positive electrode active material, which is capable of efficiently removing components other than the positive electrode active material from the mixture after heating. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a flow diagram of step (3) of one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] (Method of manufacturing recycled positive electrode active material) A method for producing a recycled positive electrode active material will be described below.

[0014] The method for producing a recycled positive electrode active material according to an embodiment of the present invention includes the following steps. Step (1): A step of mixing a positive electrode mixture containing a positive electrode active material powder and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. Step (2): Heating the mixture to obtain a heated mixture containing a heated positive electrode active material powder. Step (3): removing components other than the heated positive electrode active material powder from the heated mixture. Step (3) is (A1) a sub-step of contacting the heated mixture or the heated mixture from which components other than the heated positive electrode active material powder have been partially removed with a liquid containing water to obtain a slurry S1 containing the heated positive electrode active material powder; (A2) a sub-step of wet-classifying the heated positive electrode active material powder in the slurry S1 to obtain a slurry S2 containing the heated positive electrode active material powder having a relatively small average particle size and a slurry S3 containing the heated positive electrode active material powder having a relatively large average particle size; and (A3) a sub-step of subjecting the slurry S3 to solid-liquid separation.

[0015] Each step in this embodiment will be described in detail below.

[0016] Pre-process (A): Positive electrode composite preparation process First, a positive electrode mixture containing a positive electrode active material powder and a carbon-containing material is prepared.

[0017] In the positive electrode mixture, the positive electrode active material powders may be bound to each other by a binder. The positive electrode mixture may contain an electrolyte and / or a conductive material in addition to the positive electrode active material powder and the binder. When the positive electrode mixture contains a conductive material, the positive electrode active material powder and the conductive material may be bound to each other by a binder. The electrolyte is a component derived from the electrolyte of the battery and impregnated into the positive electrode mixture.

[0018] <Cathode active material> Examples of the positive electrode active material are composite compounds containing lithium, oxygen, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, yttrium, niobium, molybdenum, silver, indium, tungsten, or the like as constituent elements.

[0019] The positive electrode active material may be composed of only a single compound, or may be composed of a plurality of compounds.

[0020] An example of a suitable positive electrode active material is a composite oxide containing one or more elements selected from the following element group 1 and one or more elements selected from element group 2. Element group 1: Ni, Co, Mn, Fe, Al, P Element group 2: Li, Na, K, Ca, Sr, Ba, Mg

[0021] Among them, the positive electrode active material is preferably represented by the following chemical formula (Formula A).

[0022] Li 1+a M 2 b M 1 M T c O 2+d X e However, M2 represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba, and Mg, M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P, M T represents at least one element selected from the group consisting of transition metal elements other than Ni, Co, Mn, and Fe, X represents at least one element selected from the group consisting of non-metal elements excluding O and P, -0.4 < a < 1.5, 0 ≤ b < 0.5, 0 ≤ c < 0.5, -0.5 < d < 1.5, 0 ≤ e < 0.5 are satisfied.

[0023] M T is preferably at least one element selected from the group consisting of Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, Ca, Sr, Ba, Ge, Cr, Sc, Y, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, and In. Examples of X are F, S, Cl, Br, I, Se, Te, and N.

[0024] The positive electrode active material is preferably a composite oxide containing at least Li and Ni.

[0025] Also, in the positive electrode active material, the molar fraction of Ni in M 1 is more preferably 0.3 to 0.95.

[0026] The crystal structure of the composite oxide as the positive electrode active material is not particularly limited, but a layered structure is preferred, and a hexagonal or monoclinic crystal structure is more preferred.

[0027] The hexagonal crystal structure is P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P 31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P63 , P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm and P63 / mmc.

[0028] The monoclinic crystal structure belongs to any one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c and C2 / c.

[0029] Furthermore, it preferably belongs to the space group R-3m contained in a hexagonal crystal structure or the space group C2 / m contained in a monoclinic crystal structure.

[0030] The crystal structure of the positive electrode active material is identified from a powder X-ray diffraction pattern obtained by powder X-ray diffraction measurement using CuKα radiation as a radiation source.

[0031] The particle size of the positive electrode active material powder in the positive electrode mixture is not particularly limited, but is usually about 0.001 to 100 μm. The particle size distribution of the positive electrode active material powder can be measured using a laser diffraction scattering particle size distribution measuring device (e.g., Malvern Mastersizer 2000). From the obtained particle size distribution, a volume-based cumulative particle size distribution curve is created, and the particle size (D50) value at 50% accumulation from the fine particle side can be regarded as the average particle size of the positive electrode active material powder.

[0032] [Carbon-containing materials] Examples of the carbon-containing material contained in the positive electrode mixture include a binder, a conductive material (carbon-based conductive material), and an electrolyte. When the positive electrode mixture contains a binder, particles of the positive electrode active material may be bound to each other by the binder in the positive electrode mixture.

[0033] <Conductive material> Examples of the conductive material include metal-based conductive materials such as metal particles, and carbon-based conductive materials made of carbon materials.

[0034] Examples of carbon-based conductive materials are specifically graphite powder, carbon black (eg, acetylene black), and fibrous carbon materials (eg, graphitized carbon fibers, carbon nanotubes).

[0035] The carbon-based conductive material may be a single carbon material, or may be composed of a plurality of carbon materials.

[0036] The specific surface area of ​​the carbon material used as the carbon-based conductive material is usually 0.1 to 500 m 2 / g.

[0037] In this case, the conductive material is 30m 2 / g or more, it can be made of only carbon-based conductive materials 2 / g or more of carbon black, 2 / g or more.

[0038] When an activation treatment agent containing an alkali metal compound having an oxidizing power, which will be described later, is used, the speed of the oxidation treatment of the carbon-based conductive material can be increased, and even carbon materials having a small specific surface area can sometimes be oxidized.

[0039] <Binding material> Examples of the binder (pre-activation treatment binder) contained in the positive electrode mixture are thermoplastic resins, and specific examples thereof include fluororesins such as polyvinylidene fluoride (hereinafter sometimes referred to as PVdF), polytetrafluoroethylene (hereinafter sometimes referred to as PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers; polyolefin resins such as polyethylene and polypropylene; and styrene-butadiene copolymers (hereinafter sometimes referred to as SBR); and may be a mixture of two or more of these.

[0040] There is no particular limitation on the amounts of the positive electrode active material powder, conductive material, and binder in the positive electrode mixture. The amount of the binder can be 0.5 to 30 parts by weight, or may be 1 to 5 parts by weight, relative to 100 parts by weight of the positive electrode active material powder. The amount of the conductive material can be 0, or may be 0 to 50 parts by weight, or may be 1 to 10 parts by weight, relative to 100 parts by weight of the positive electrode active material powder. The content of the binder in the positive electrode mixture may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the binder may be 0.5 parts by mass or more, 1 part by mass or more, or 2 parts by mass or more. The content of the binder may be 30 parts by mass or less, 10 parts by mass or less, or 5 parts by mass or less. From these viewpoints, the content of the binder may be 0.5 to 30 parts by mass, 1 to 10 parts by mass, 1 to 5 parts by mass, or 2 to 5 parts by mass. The content of the conductive material in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the conductive material may be 0 parts by mass or more, more than 0 parts by mass, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more. The content of the conductive material may be 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less. From these viewpoints, the content of the conductive material may be 0 to 50 parts by mass, more than 0 parts by mass and 40 parts by mass or less, 1 to 30 parts by mass, 1 to 10 parts by mass, 3 to 20 parts by mass, or 5 to 10 parts by mass.

[0041] The positive electrode mixture may contain a metal-based conductive material such as metal particles and / or an electrolyte in addition to the positive electrode active material and the carbon-containing material. When the positive electrode mixture contains a binder and a conductive material, the particles of the positive electrode active material and the conductive material may be bound to each other by the binder. The electrolyte is a component that is derived from the electrolyte of the battery and is impregnated into the positive electrode mixture. The positive electrode mixture may contain a fluorine compound derived from the binder and / or the electrolyte (e.g., the electrolyte in the electrolyte).

[0042] <Electrolyte> Examples of the electrolyte are LiPF6, LiBF4, LiClO4, LiN(SO2CF3)2, LiN(SO2F)2, and LiCF3SO3. The amount of the electrolyte contained in the positive electrode mixture is not limited, but may be 0.0005 to 7 mass %.

[0043] The positive electrode mixture may contain a solvent derived from the electrolyte, for example, dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate.

[0044] Such a positive electrode mixture can be obtained by separating and recovering the positive electrode mixture from a waste positive electrode having a current collector and a positive electrode mixture layer.

[0045] The "scrap positive electrodes" can be positive electrodes recovered from discarded batteries and waste positive electrodes generated during the manufacturing process of positive electrodes and batteries. The discarded batteries can be used batteries or unused but non-standard batteries. The waste positive electrodes can be the ends of positive electrodes generated during the manufacturing process of batteries and non-standard positive electrodes. In addition, the waste positive electrode can be a waste positive electrode mixture that is not attached to a current collector and is generated during the manufacturing process of the positive electrode mixture.

[0046] The waste positive electrode has a current collector which is a metal foil such as an aluminum foil or a copper foil, and a positive electrode mixture layer provided on the current collector. The positive electrode mixture layer may be provided on one side or both sides of the current collector.

[0047] Methods for separating the positive electrode mixture from a waste positive electrode having a positive electrode mixture layer and a current collector include a method for mechanically peeling the positive electrode mixture layer from the current collector (for example, a method for scraping the positive electrode mixture from the current collector), a method for penetrating a solvent into the interface between the positive electrode mixture layer and the current collector to peel the positive electrode mixture layer from the current collector, a method for dissolving the current collector using an alkaline or acidic aqueous solution to separate the positive electrode mixture layer, etc. The method for mechanically peeling the positive electrode mixture layer from the current collector is preferred.

[0048] Previous process (B): Positive electrode mixture cleaning process Next, when the positive electrode composite contains an electrolyte, it is preferable to bring the prepared positive electrode composite into contact with an electrolyte washing solvent to remove at least a part of the electrolyte from the positive electrode composite. Specifically, the positive electrode composite containing the positive electrode active material powder, the binder, and the electrolyte is brought into contact with the electrolyte washing solvent to obtain a slurry containing a solid component and a liquid component, and then the slurry is separated into the solid component and the liquid component.

[0049] The solid-liquid separation is a process for separating the slurry into a liquid component and a solid component. The method for solid-liquid separation may be a conventionally known method, such as filtration or centrifugation.

[0050] The electrolyte cleaning solvent is not particularly limited, and examples thereof include carbonates such as ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate; water; ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone; and alcohols such as ethanol, methanol, propanol, and isopropyl alcohol.

[0051] The positive electrode mixture can be brought into contact with the electrolyte cleaning solvent in a known powder-liquid contact device, such as a stirring tank.

[0052] In the step of contacting the positive electrode mixture with the electrolyte washing solvent, it is preferable to obtain a slurry by stirring the positive electrode mixture and the electrolyte washing solvent. The peripheral speed of the tip of the stirring blade can be 0.1 to 1.0 m / s.

[0053] In the washing step of the positive electrode mixture, after solid-liquid separation, the obtained solid component may be rinsed. Rinsing is an operation in which the obtained solid component is contacted with the electrolyte washing solvent again to obtain a slurry, and then the slurry is separated again into a solid component and a liquid component. In washing the positive electrode mixture, rinsing may be performed multiple times. The slurry concentration in rinsing can be the same as above. In rinsing, the slurry can be stirred as described above.

[0054] The above-mentioned washing can sufficiently remove the electrolyte from the positive electrode mixture. For example, if the electrolyte remains, the following reaction occurs, and the structure of the positive electrode active material changes from a layered rock salt structure to a spinel structure. LiPF6+16LiMO2+2O2→6LiF+Li3PO4+8LiM2O4 Furthermore, when lithium carbonate is included as an activator, lithium is also consumed through the following reaction: LiPF6+4Li2CO3→6LiF+Li3PO4+4CO2

[0055] The separated solid component may be dried, if necessary, by reducing pressure and / or heating to remove the electrolyte washing solvent. The heating temperature may be 50 to 200°C.

[0056] Step (1): Activation treatment agent mixing step Next, an activation treatment agent containing one or more types of alkaline compounds is mixed with the prepared positive electrode mixture to obtain a mixture.

[0057] The method for mixing the positive electrode mixture and the activation treatment agent may be either dry mixing or wet mixing, or a combination of these mixing methods may be used, and the mixing order is not particularly limited.

[0058] During mixing, it is preferable to use a mixer equipped with mixing media such as balls and to carry out a pulverizing and mixing step, which can improve the mixing efficiency.

[0059] As a mixing method, dry mixing is preferred because it allows mixing to be performed more easily. In dry mixing, a V-type mixer, a W-type mixer, a ribbon mixer, a drum mixer, a powder mixer equipped with an internal stirring blade, a ball mill, a vibration mill, or a combination of these devices can be used.

[0060] As a mixer used for dry mixing, a powder mixer equipped with an internal stirring blade is preferable, and a specific example thereof is a Loedige Mixer (manufactured by Matsubo Corporation).

[0061] The activation treatment agent used in this step will be described in detail below.

[0062] <Activation treatment agent> The activation treatment agent contains one or more alkali metal compounds. The activation treatment agent preferably contains at least one compound selected from the group consisting of potassium compounds and sodium compounds. Here, potassium and / or sodium may be referred to as alkali metal element X. The activation treatment agent may contain an alkali metal compound containing another alkali metal such as Li in addition to the potassium compound and / or sodium compound.

[0063] When the activation treatment agent comes into contact with the positive electrode active material, the positive electrode active material can be activated. In particular, when the alkali metal compound in the activation treatment agent contains a molten portion, the contact between the molten portion and the positive electrode active material is improved, and the activation of the positive electrode active material is further promoted.

[0064] In addition, the positive electrode mixture may contain a compound containing fluorine derived from the binder and / or the electrolyte, but by contacting the compound containing fluorine with the activation treatment agent, the fluorine component is stabilized as an alkali metal fluoride, so that the generation of corrosive gases such as hydrogen fluoride can be suppressed. Note that it is desirable to prevent the generation of hydrogen fluoride, since it reduces the activity of the positive electrode active material.

[0065] The proportion of all alkali metal compounds in the activation treatment agent is appropriately set taking into consideration the type of alkali metal compound and the type of target positive electrode active material, etc., but is usually 50% by weight or more, preferably 70% by weight or more (including 100% by weight) of the total weight of the activation treatment agent. The concentration of at least one alkali metal selected from the group consisting of potassium and sodium among the alkali metals contained in the alkali metal compound can be adjusted arbitrarily within the range of 0 to 100 mol%, but is preferably 10 mol% or more, more preferably 20 mol% or more, and is preferably 90 mol% or less, more preferably 80 mol% or less.

[0066] Examples of alkali metal compounds that are components of the activation treatment agent include hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, bromates, molybdates, and tungstates of alkali metals. These can be used alone or in combination as components of the activation treatment agent.

[0067] Specific examples of suitable alkali metal compounds include hydroxides such as LiOH, NaOH, KOH, RbOH, CsOH, etc.; Borates such as LiBO2, NaBO2, KBO2, RbBO2, CsBO2; Carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, CsCO3; Oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O; Peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, Cs2O2; Superoxides such as LiO2, NaO2, KO2, RbO2, CsO2; Nitrates such as LiNO3, NaNO3, KNO3, RbNO3, CsNO3; Phosphates such as Li3PO4, Na3PO4, K3PO4, Rb3PO4, Cs3PO4; Sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, Cs2SO4; Chlorides such as LiCl, NaCl, KCl, RbCl, CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, CsBr, etc.; Vanadates such as LiVO3, NaVO3, KVO3, RbVO3, CsVO3; Molybdates such as Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, CsMoO4; Tungstates such as Li2WO4, Na2WO4, K2WO4, Rb2WO4, and CsWO4.

[0068] Here, in order to further enhance the activation effect of the positive electrode active material, the activation treatment agent may contain, in addition to at least one compound selected from the group consisting of potassium compounds and sodium compounds, the same alkali metal element as the alkali metal element contained in the positive electrode active material in the positive electrode mixture.

[0069] That is, when the positive electrode active material in the positive electrode mixture is a lithium composite oxide, the activation treatment agent preferably contains a lithium compound in addition to at least one compound selected from the group consisting of potassium compounds and sodium compounds. Suitable lithium compounds include LiOH, LiBO2, Li2CO3, Li2O, Li2O2, LiO2, LiNO3, Li3PO4, Li2SO4, LiCl, LiVO3, LiBr, Li2MoO4, and Li2WO4.

[0070] The activation treatment agent may contain a compound other than an alkali metal compound as necessary. Examples of the compound other than an alkali metal compound include alkaline earth metal compounds containing alkaline earth metal elements such as magnesium, calcium, barium, etc. The alkaline earth metal compound is contained in the activation treatment agent together with the alkali metal compound for the purpose of controlling the melting start temperature of the activation treatment agent.

[0071] In addition, the content of compounds other than the alkali metal compound in the activation treatment agent is selected within a range that does not significantly suppress the effects derived from the above-mentioned molten alkali metal compound, and can be less than 50 weight % of the total weight of the activation treatment agent.

[0072] The amount of the activation treatment agent added in the mixture of the positive electrode mixture and the activation treatment agent is preferably 0.001 to 100 times, and more preferably 0.05 to 1 time, the weight of the positive electrode active material contained in the positive electrode mixture.

[0073] When the activation treatment agent contains a potassium compound and a lithium compound, the ratio of the lithium content (molar) to the potassium content (molar) (lithium content / potassium content) may be 0.01 to 100, 0.1 to 10, or 0.2 to 4, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.

[0074] When the activation treatment agent contains a sodium compound and a lithium compound, the ratio of the lithium content (molar basis) to the sodium content (molar basis) (lithium content / sodium content) may be 0.01 to 100, 0.1 to 10, or 0.2 to 4, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.

[0075] When the activation treatment agent contains a potassium compound, the potassium content (molar) contained in the activation treatment agent may be 1% or more and less than 500%, 10% or more and less than 400%, 50% or more and less than 300%, 100% or more and less than 250%, or 150% or more and less than 250% of the fluorine content (molar) contained in the positive electrode composite, from the viewpoint of making the charge / discharge characteristics of a battery manufactured using the recycled positive electrode active material more similar to the charge / discharge characteristics of a battery manufactured using an unused positive electrode active material.

[0076] When the activation treatment agent contains a sodium compound, the sodium content (molar) contained in the activation treatment agent may be 1% or more and less than 500%, 10% or more and less than 400%, 50% or more and less than 300%, 100% or more and less than 250%, or 150% or more and less than 250% of the fluorine content (molar) contained in the positive electrode composite, from the viewpoint of making the charge / discharge characteristics of a battery manufactured using the recycled positive electrode active material more similar to the charge / discharge characteristics of a battery manufactured using an unused positive electrode active material.

[0077] The number of moles of the alkali metal compound in the activation treatment agent in the mixture of the positive electrode composite and the activation treatment agent can be added so that the number of moles of the alkali metal element is 0.001 to 200 times the number of moles of the positive electrode active material (e.g., Formula A) contained in the positive electrode composite.

[0078] By appropriately controlling the ratio of the activation treatment agent in the mixture, the cost of recovering the positive electrode active material powder from the positive electrode mixture can be reduced, the oxidative decomposition rate of the carbon-based conductive material and the binder can be increased, the effect of preventing the generation of corrosive gas during the heating process can be improved, and the discharge capacity of the battery manufactured using the obtained positive electrode active material can be further increased.

[0079] In addition, it is preferable that at least one of the alkali metal compounds contained in the activation treatment agent is an alkali metal compound that exhibits alkalinity when dissolved in water. When an activation treatment agent containing such an alkali metal compound is dissolved in pure water, the pH of the solution becomes greater than 7. Hereinafter, such an activation treatment agent may be referred to as an "alkaline activation treatment agent."

[0080] By using an alkaline activation treatment agent, the generation of corrosive gas during the heating process can be further suppressed, so that the discharge capacity of the battery manufactured using the recovered positive electrode active material can be further increased. In addition, by using an alkaline activation treatment agent, the treatment speed of the carbon-based conductive material and the binder can be increased.

[0081] Examples of alkali metal compounds that exhibit alkalinity when dissolved in water and are contained in an alkaline activation treatment agent include hydroxides, carbonates, hydrogen carbonates, oxides, peroxides, and superoxides of alkali metals.Specific examples include LiOH, NaOH, KOH, RbOH, and CsOH; Li2CO3, Na2CO3, K2CO3, RbCO3, CsCO3; LiHCO3, NaHCO3, KHCO3, RbHCO3, CsHCO3; Li2O, Na2O, K2O, Rb2O, and Cs2O; Li2O2, Na2O2, K2O2, Rb2O2, and Cs2O2; LiO2, NaO2, KO2, RbO2, and CsO2; and these may be contained in the activation treatment agent alone or in combination.

[0082] In addition, when the conductive material contained in the positive electrode composite is a carbon-based conductive material, at least one of the alkali metal compounds contained in the activation treatment agent may be an alkali metal compound having an oxidizing power that oxidizes and decomposes the carbon-based conductive material at the temperature of the heating step. Hereinafter, an activation treatment agent containing such an alkali metal compound may be referred to as an "activation treatment agent having an oxidizing power."

[0083] Use of an activation treatment agent having such oxidizing power is particularly effective in promoting the oxidation of the conductive material, which is a carbon material, to carbon dioxide, and promoting the oxidation of the binder, which is a hydrocarbon material, to carbon dioxide and water vapor, and can further increase the discharge capacity of a battery manufactured using the obtained positive electrode active material, and can also improve the effect of preventing the generation of corrosive gases during the heating process in some cases.

[0084] Alkali metal compounds having the oxidizing power necessary to oxidize the carbonaceous conductive material and the hydrocarbons to carbon dioxide and water vapor include alkali metal peroxides, superoxides, nitrates, sulfates, vanadates, and molybdates, which may be used alone or in combination of two or more.

[0085] Specifically, these include Li2O2, Na2O2, K2O2, Rb2O2, Cs2O2; LiO2, NaO2, KO2, RbO2, CsO2; LiNO3, NaNO3, KNO3, RbNO3, CsNO3; Li2SO4, Na2SO4, K2SO4, Rb2SO4, Cs2SO4; LiVO3, NaVO3, KVO3, RbVO3, CsVO3; Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, CsMoO4;

[0086] Details of the oxidizing power of these alkali metal compounds are described in JP 2012-186150 A.

[0087] The alkali metal compound may be a carbonate or sulfate, or at least one selected from the group consisting of Li2CO3, Na2SO4, Na2CO3, and K2CO3, from the viewpoint of making it easier to make the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to those of a battery produced using an unused positive electrode active material.

[0088] Process (2): Heating process The heating step is a step of heating the mixture obtained in step (1) (hereinafter, sometimes referred to as the "mixture before heating"). The mixture obtained in this heating step is sometimes referred to as the "mixture after heating".

[0089] The mixture before heating may be heated to a temperature equal to or higher than the melting initiation temperature (Tmp) of the activation treatment agent, or may be heated to a temperature lower than the melting initiation temperature (Tmp) of the activation treatment agent.

[0090] In this specification, the temperature of the heating step is lower than the melting start temperature of the activation treatment agent means that the temperature of the heating step is maintained at a temperature lower than the melting start temperature of the activation treatment agent (heating is performed at a temperature maintained lower than the melting start temperature of the activation treatment agent). In addition, the temperature of the heating step is lower than the melting start temperature of the activation treatment agent means that the temperature of the heating step is not set to a temperature equal to or higher than the melting start temperature of the activation treatment agent. The temperature of the heating step (maximum temperature in the heating space) may be, for example, 300 to 600°C, 350 to 575°C, or 400 to 550°C.

[0091] The "melting start temperature (Tmp) of the activation treatment agent" means the lowest temperature at which a part of the activation treatment agent exhibits a liquid phase.

[0092] The melting start temperature (Tmp) of the activation treatment agent is a value determined by differential thermal analysis (DTA). That is, 5 mg of the mixture before heating is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10°C / min), and the temperature at which the DTA signal shows an endothermic peak is defined as the melting start temperature (Tmp).

[0093] The melting start temperature (Tmp) of the activation treatment agent is preferably 700° C. or less, and more preferably 600° C. or less. There is no lower limit to the melting start temperature (Tmp) of the activation treatment agent, but it may be, for example, 150° C.

[0094] The melting point of the activation treatment agent means the lowest temperature at which a part of the activation treatment agent becomes liquid when the activation treatment agent alone is heated. By mixing the positive electrode composite material and the activation treatment agent, the melting start temperature (Tmp) of the activation treatment agent becomes lower than the melting point of the activation treatment agent.

[0095] The melting point of the activation treatment agent is a value determined by differential thermal analysis (DTA). Specifically, 5 mg of the activation treatment agent is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10° C. / min), and the temperature at which the DTA signal shows an endothermic peak is defined as the melting point of the activation treatment agent.

[0096] The atmosphere for heating is not particularly limited, and may be an oxygen-containing gas such as air, nitrogen, argon, or carbon dioxide. The pressure of the atmosphere is not particularly limited, and may be atmospheric pressure, a reduced pressure atmosphere, or a pressurized atmosphere.

[0097] (Heating above the melting temperature (Tmp) of the activation treatment agent) In the step (2), the mixture before heating is heated to a temperature equal to or higher than the melting initiation temperature (Tmp) of the activation treatment agent as described above, whereby the following effects are achieved.

[0098] The contact of the molten activation treatment agent with the positive electrode active material can suppress deterioration of the crystal structure of the positive electrode active material, and in some cases can even restore the crystal structure.

[0099] When the molten activation treatment agent comes into contact with a carbon-containing material (carbon-based conductive material or binder), the rate of oxidative decomposition of the conductive material and binder is increased. Furthermore, when the molten activation treatment agent comes into contact with the binder and a fluorine compound derived from the electrolyte, the fluorine component is stabilized as an alkali metal fluoride, preventing the generation of hydrogen fluoride, which is a corrosive gas, and suppressing deterioration of the crystal structure of the positive electrode active material.

[0100] Furthermore, when the activation treatment agent contains the same alkali metal as the positive electrode active material, it is also possible to supply the alkali metal that is insufficient for the positive electrode active material.

[0101] The temperature of the heating step is preferably higher than the melting point of the alkali metal compound contained in the activation treatment agent. The melting point of the alkali metal compound may be lower than the melting point of each compound alone by mixing multiple types of compounds. When the activation treatment agent contains two or more types of alkali metal compounds, the eutectic point is the melting point of the alkali metal compound.

[0102] (Heating below the melting temperature (Tmp) of the activation treatment agent) In step (2), the mixture before heating is heated to a temperature below the melting temperature of the activation treatment agent, thereby suppressing deterioration of the crystal structure of the positive electrode active material caused by heating at high temperatures, and making it easier to achieve charge / discharge characteristics equivalent to those of a battery manufactured using an unused positive electrode active material. In addition, the crystal structure can be restored by heating the mixture before heating together with the activation treatment agent.

[0103] When the heated activation treatment agent comes into contact with a carbon-containing material (such as a carbon-based conductive material or binder), the rate of oxidative decomposition of the conductive material and the binder is increased. Furthermore, when the heated activation treatment agent comes into contact with a fluorine compound derived from the binder and the electrolyte, the fluorine component is stabilized as an alkali metal fluoride, preventing the generation of hydrogen fluoride, which is a corrosive gas, and suppressing deterioration of the crystal structure of the positive electrode active material.

[0104] The time for which the mixture is heated at a temperature lower than the melting initiation temperature of the activation treatment agent may be determined depending on the amount of the mixture before heating, etc. The time for which the mixture is heated at a temperature lower than the melting initiation temperature of the activation treatment agent may be, for example, 1 minute to 24 hours.

[0105] The temperature of the heating step and the holding time at that temperature can be appropriately adjusted depending on the types and combinations of the positive electrode active material, conductive material, binder, alkali metal compound and other compounds contained in the activation treatment agent that constitute the positive electrode mixture. Usually, the temperature is in the range of 100 to 1500°C, and the holding time is about 10 minutes to 24 hours.

[0106] After the heating step, the mixture can be cooled to any temperature, such as, for example, about room temperature, if desired. In this manner, a heated mixture containing the heated positive electrode active material powder is obtained.

[0107] Step (3): Removing components other than the positive electrode active material powder from the mixture after heating. Step (3) is a step of removing components other than the heated positive electrode active material powder from the heated mixture obtained in the heating step (2).

[0108] The mixture after heating contains the positive electrode active material powder after heating, as well as components derived from the activation treatment agent (such as alkali metal compounds), undecomposed carbon-containing materials (such as conductive materials and binders), and other undecomposed substances of the positive electrode mixture. In addition, when the positive electrode mixture contains an electrolyte solution containing a fluorine component, the mixture may contain a fluorine component derived from the electrolyte.

[0109] Removing components other than the positive electrode active material powder from the mixture after heating includes multiple removal steps, and therefore "removing components other than the positive electrode active material powder from the mixture after heating" also includes an operation of further removing components other than the positive electrode active material powder from the mixture after heating from which components other than the positive electrode active material powder have been partially removed (sometimes referred to as a partially removed mixture).

[0110] One example of a method for removing components other than the positive electrode active material powder from the heated mixture or the partially removed mixture is a slurrying and solid-liquid separation method in which a liquid containing water is added to the heated mixture or the partially removed mixture to form a slurry, and then the slurry is separated into solid and liquid. Another example of the above method is a vaporization separation method in which the heated mixture or the partially removed mixture is heated to vaporize and separate the components other than the heated positive electrode active material powder.

[0111] In this embodiment, step (3) includes performing at least one slurrying and solid-liquid separation process, and in at least one of the slurrying and solid-liquid separation processes, wet classification is performed in the slurry after slurrying and before solid-liquid separation.

[0112] That is, step (3) is as shown in FIG. (A1) a sub-step of contacting the heated mixture or the partially removed mixture with a liquid containing water to obtain a slurry S1 containing a heated positive electrode active material powder; (A2) a sub-step of wet-classifying the heated positive electrode active material powder in the slurry S1 to obtain a slurry S2 containing the heated positive electrode active material powder having a relatively small average particle size and a slurry S3 containing the heated positive electrode active material powder having a relatively large average particle size; and (A3) a sub-step of subjecting the slurry S3 to solid-liquid separation.

[0113] In the step (A1), a liquid containing water is brought into contact with the mixture after heating or the partially removed mixture to obtain a slurry S1 containing the positive electrode active material powder after heating.

[0114] As described above, the mixture after heating contains, in addition to the positive electrode active material powder after heating, components derived from the activation treatment agent (such as alkali metal compounds), undecomposed conductive material and binder, and other undecomposed materials of the positive electrode composite. In addition, when the positive electrode composite contains an electrolyte solution containing a fluorine component, the mixture may contain a fluorine component derived from the electrolyte. By adding a liquid containing water to the mixture to form a slurry, the components other than the positive electrode active material powder after heating are dissolved in the liquid.

[0115] The liquid used for slurrying is not particularly limited as long as it contains water. The amount of water in the liquid may be 50% by mass or more. In order to increase the solubility of water-soluble components or to increase the processing speed, components other than water may be added to the liquid to adjust the pH.

[0116] Suitable examples of the liquid containing water include pure water and alkaline cleaning liquid. Examples of the alkaline cleaning liquid include an aqueous solution of at least one anhydride selected from the group consisting of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, and ammonium carbonate, and a hydrate thereof. Ammonia can also be used as the alkali.

[0117] The obtained slurry contains a solid phase mainly containing the positive electrode active material powder after heating and a liquid phase containing water-soluble components other than the positive electrode active material powder after heating. The liquid components include an alkali metal component derived from the activation treatment agent and / or a fluorine component derived from the binder and the electrolyte.

[0118] The amount of liquid added to the heated mixture or the partially removed mixture is appropriately determined taking into consideration the amounts of the heated positive electrode active material powder and water-soluble components other than the positive electrode active material powder contained in each mixture.

[0119] In the sub-step (A1), it is preferable to obtain a slurry S1 by stirring the mixture after heating or the partially removed mixture with a liquid containing water. This promotes dissolution of the water-soluble components. The peripheral speed of the tip of the stirring blade is preferably 0.1 to 0.9 m / s.

[0120] In sub-step (A2), the heated positive electrode active material powder in the slurry S1 is wet-classified to obtain a slurry S2 containing a heated positive electrode active material powder having a relatively small average particle size, and a slurry S3 containing a heated positive electrode active material powder having a relatively large average particle size.

[0121] The specific means for wet classification is not particularly limited, and may be a wet cyclone or a wet sieve. An example of the wet sieve is a so-called slurry screener, which discharges fine powder in a mesh screen cylinder to the outside of the screen by centrifugal force generated by the rotation of a screw arranged in the mesh screen cylinder.

[0122] The average particle size may be D50 in the volume-based particle size distribution measured by a laser diffraction particle size distribution analyzer. The average particle size in the slurry S3 may be 10 to 20 μm. The difference between the average particle size in the slurry S3 and the average particle size in the slurry S2 may be 1 to 10 μm.

[0123] In step (A3), the slurry S3 is subjected to solid-liquid separation. Solid-liquid separation is a process for separating the slurry into a liquid phase and a solid phase. The method for solid-liquid separation may be a conventionally known method, for example, filtration or centrifugation.

[0124] In this embodiment, the step (3) has the sub-steps (A1) to (A3), and thus the following effects are achieved. First, by going through step (A1), water-soluble components other than the positive electrode active material powder after heating are removed from the solid phase in the slurry and transferred to the liquid phase, and then, by going through step (A3), the obtained solid phase is one from which components other than the positive electrode active material after heating have been removed.

[0125] In addition, the positive electrode active material powder in the positive electrode mixture obtained from the waste positive electrode tends to have a broader particle size distribution or a smaller average particle size (e.g., D50) due to crack generation due to expansion and contraction accompanying charging and discharging. According to this embodiment, the positive electrode active material powder after heating in the slurry S1 is subjected to a sub-step (A2), that is, the slurry S2 containing the positive electrode active material powder after heating having a relatively small average particle size and the slurry S3 containing the positive electrode active material powder after heating having a relatively large average particle size are obtained, and the slurry S3 is then subjected to solid-liquid separation in the sub-step (A3). Therefore, the amount of fine powder in the positive electrode active material powder after heating in the slurry S3 is reduced, so that during solid-liquid separation in the slurry S3, a flow path through which the liquid is discharged in the solid-phase cake is easily secured, and the drainage of the liquid from the solid-phase cake is improved, resulting in effects such as a reduction in the time required for solid-liquid separation and / or a reduction in the moisture content in the obtained solid-phase cake.

[0126] Furthermore, when the solid cake is subsequently dried as required, a flow path for water vapor to escape from within the solid cake is easily secured, so that the amount of energy, time, etc. required for drying can be reduced.

[0127] The above sub-steps (A1) to (A3) may be carried out at least once in the step (3) of removing components other than the heated positive electrode active material powder from the heated mixture or the partially removed mixture.

[0128] For example, the sub-step (A1) may be a step of bringing a liquid containing water into contact with the "heated mixture" to obtain a slurry S1 containing the heated positive electrode active material powder.

[0129] Even if such sub-steps (A1) to (A3) are performed once, the solid phase obtained by solid-liquid separation of the slurry S3 in the sub-step (A3) often contains trace amounts of components other than the positive electrode active material powder after heating, and corresponds to the above-mentioned "partially removed mixture." Therefore, the solid phase obtained in the sub-step (A3) may be directly subjected to a drying step described below, but a sub-step of removing remaining components other than the positive electrode active material powder from the "partially removed mixture" may also be performed.

[0130] The step of removing components other than the remaining positive electrode active material powder from the "partially removed mixture" may be the vaporization separation method described above, but is preferably the slurrying and solid-liquid separation method (also called rinsing in this case) described above.

[0131] For example, step (3) may include, after sub-step (A3), (B1) a sub-step of contacting the “partially removed mixture” with a liquid containing water to obtain a slurry Q1 containing a positive electrode active material powder after heating; and (B3) a sub-step of performing solid-liquid separation of the slurry Q1 may be included, which results in a higher purity of the solid phase obtained.

[0132] The combination of sub-steps (B1) and (B3) carried out after sub-step (A3) may be carried out multiple times.

[0133] Between the substeps (B1) and (B3), a substep (B2) may be provided in which the heated positive electrode active material powder in the slurry Q1 is wet-classified to obtain a slurry Q2 containing the heated positive electrode active material powder having a relatively small average particle size, and a slurry Q3 containing the heated positive electrode active material powder having a relatively large average particle size. In this case, the slurry Q3 may be subjected to solid-liquid separation in the substep (B3).

[0134] The solid phase obtained in substep (B3) can be subjected to a drying step which will be described below.

[0135] In addition, the above sub-steps (A1) to (A3) may be performed in a step of removing components other than the heated positive electrode active material powder from the “partially removed mixture” rather than in a step of removing components other than the heated positive electrode active material powder from the “heated mixture”. In this case, the step of removing components other than the post-heating positive electrode active material powder from the "post-heating mixture" may be the vaporization separation method described above, but is preferably the slurrying and solid-liquid separation method described above.

[0136] In this specification, the positive electrode active material powder that has undergone steps (1) to (3) is referred to as recycled positive electrode active material powder. The recycled positive electrode active material powder that has undergone steps (1) to (3) can be suitably used for manufacturing a positive electrode or the like. The manufacturing method for the recycled positive electrode active material powder may include additional steps before and after steps (1) to (3). In this specification, the positive electrode active material powder that has undergone additional steps other than steps (1) to (3) is also referred to as recycled positive electrode active material powder. Examples of additional steps other than steps (1) to (3) are pre-steps (A) and (B) performed before step (1), and the following steps (4) and (5) performed after step (3), for example after step (3a).

[0137] Process (4): Drying process Step (4) is a step of removing water from the solid component by exposing the solid phase obtained in step (3) to a heating and / or reduced pressure environment.

[0138] The heating temperature is preferably 100°C or higher to remove water. It is more preferably 150°C or higher to remove water sufficiently. In particular, a temperature of 250°C or higher is preferable because the discharge capacity of a battery manufactured using the obtained positive electrode active material is further increased. The temperature in the drying step may be constant, or may be changed stepwise or continuously. The heating temperature range may be, for example, 10°C or higher and less than 900°C.

[0139] The ultimate pressure range of the reduced pressure is, for example, 1.0×10 -10 ~1.0×10 3 It can be Pa.

[0140] Step (5): Annealing (re-firing) step Step (5) is preferably a step of heat-treating the solid component after step (4) (sometimes referred to as the dried solid component). When the mixture before heating is heated to a melting initiation temperature or higher in step (2), the annealing step may be, for example, a step of heat-treating the dried solid component at less than 900°C.

[0141] When the mixture before heating is heated at a temperature lower than the melting initiation temperature in step (2), the annealing step may be, for example, a step of heating the dried solid component at a temperature higher than that in step (2). In this case, the temperature at which the dried solid component is heated may be more than 700° C., 750° C. or higher, 800° C. or higher, 850° C. or higher, or 900° C. or higher, from the viewpoint of vaporizing components other than the positive electrode active material and removing impurities, and from the viewpoint of making the crystallite size of the positive electrode active material sufficiently large to more easily achieve charge / discharge characteristics comparable to those of a battery manufactured using an unused positive electrode active material.

[0142] The atmosphere for the heat treatment is not limited, but an oxygen-containing atmosphere such as air is preferable. The heat treatment temperature can be 100°C or higher. The heat treatment holding time can be 1 minute to 24 hours. In particular, heating at a temperature of 350°C or higher for 0.1 to 5 hours is preferable.

[0143] The recycled positive electrode active material powder obtained from the battery mixture by using the method for producing the recycled positive electrode active material powder of the present invention can be reused in the same way as unused active material. Methods for producing positive electrodes and batteries using the recycled positive electrode active material powder are well known.

[0144] The final discharge capacity of the recycled positive electrode active material according to the embodiment of the present invention can be 150 mAh / g or more. EXAMPLES

[0145] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.

[0146] Example 1 A. Manufacturing of Positive Electrode A The positive electrode active material is Li 1.04 Ni 0.60 Co 0.20 Mn 0.20 The positive electrode active material is O2 and has a crystal structure of R-3m. Acetylene Black HS100 (manufactured by Denki Kagaku Kogyo Co., Ltd.) is used as the conductive material. The binder and solvent were prepared by adding NMP solvent to an NMP solution (manufactured by Kureha Corporation) containing 12% by weight of PVdF#1100 as the binder to obtain a predetermined ratio.

[0147] The mass ratio of the positive electrode active material, the binder, and the conductive material in the positive electrode mixture was 92: 3: 5. The blending amount of the solvent was 50 mass % with respect to the entire positive electrode mixture paste.

[0148] The positive electrode composite paste is applied onto a 20 μm thick aluminum foil 1085 (manufactured by Nippon Foil Co., Ltd.) for use as a positive electrode current collector for lithium ion secondary batteries using a doctor blade coater, and then dried to obtain a positive electrode A. The amount of positive electrode active material on the aluminum foil is 20 mg / cm. 2 Let us assume that.

[0149] B. Recovery of electrode mixture from positive electrode A From positive electrode A, the electrode mixture is mechanically peeled off from the current collector.

[0150] C. Electrolyte immersion process The peeled electrode mixture is pulverized to powder. The electrode mixture powder is added with an electrolyte solution so that the slurry concentration becomes 1500 g / L to make a slurry. Here, the electrolyte solution is a solution in which LiPF6 is dissolved as an electrolyte at a ratio of 1.0 mol / L in a 30:35:35 (volume ratio) mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate. The electrode mixture slurry is stirred for 1 minute at a maximum flow rate of 0.550 m / sec. Thereafter, the slurry is filtered to separate the solid phase, and the solid phase is further dried under reduced pressure for 24 hours to obtain an electrolyte-containing electrode mixture. The electrolyte immersion process is performed in a glove box in an argon atmosphere.

[0151] D. Cleaning process for electrolyte-containing electrode mixture The obtained electrolyte-containing electrode mixture is slurried by adding water as an electrolyte washing solvent to a slurry concentration of 5 g / L, and the mixture is stirred for 1437 minutes at a peripheral speed of the stirring blade tip of 0.942 m / s, and then the slurry is separated into a solid component and a liquid component by filtering for 3 minutes. The obtained solid component is dried under reduced pressure at 100°C for 1 hour, and the washed electrode mixture is recovered.

[0152] E. Activation treatment agent mixing process (corresponding to process (1)) After cleaning, the electrode mixture is mixed with Li2CO3 and K2SO4 as activation agents in amounts of 0.15 mol and 0.15 mol per mol of the positive electrode active material in the electrode mixture to obtain a mixture (mixture before heating). The melting point of the activation agent is 550°C.

[0153] F. Heating process (corresponding to process (2)) The obtained pre-heated mixture is placed in an alumina firing container and placed in an electric furnace. The mixture is activated at atmospheric pressure at a temperature of 700°C for a holding time of 3 hours. The heating rate is 300°C / hour, and the mixture is cooled naturally to room temperature. After cooling to room temperature, the heated mixture is collected.

[0154] G. A process for removing components other than the heated positive electrode active material powder from the heated mixture (corresponding to process (3)) The mixture after heating is pulverized, water is added, and the mixture is stirred for 1 minute to form a slurry with a concentration of 20 g / L to obtain slurry S1. The heated positive electrode active material powder in the slurry S1 is then wet classified using a slurry screener manufactured by Accor Japan Co., Ltd. to obtain slurry S2 containing the heated positive electrode active material powder with a relatively small average particle size and slurry S3 containing the heated positive electrode active material powder with a relatively large average particle size. The screen has an opening of 13 μm. The slurry is then filtered to separate it into a solid phase and a liquid phase.

[0155] H. Drying process of the positive electrode active material (corresponding to process (4)) The solid phase obtained is dried under reduced pressure at 100° C. for 1 hour.

[0156] H. Re-firing process of the positive electrode active material (corresponding to process (6)) The recovered positive electrode active material after washing is placed in an alumina firing container and placed in an electric furnace. The mixture is heated at 700°C under atmospheric pressure for 1 hour. The heating rate is 300°C / hour, and the mixture is cooled naturally to room temperature. After cooling to room temperature, the reactivated positive electrode active material is recovered.

[0157] A coin-type battery is manufactured from the recovered reactivated positive electrode active material, and a charge-discharge test is performed. The discharge capacity and internal resistance in the charge-discharge test are measured, and the initial discharge capacity recovery rate and internal resistance recovery rate are calculated.

[0158] (Reference example 1) <Production of positive electrodes> The positive electrode described below was prepared by the following procedure. A mixture was obtained by mixing 92 parts by mass of a positive electrode active material (unused positive electrode active material or recycled positive electrode active material), 3 parts by mass of PVdF (binder, manufactured by Kureha Corporation, product number: #1100), and 5 parts by mass of acetylene black (conductive material, manufactured by Denka Co., Ltd., product number: HS100). As the binder PVdF, a binder solution in which PVdF was dissolved in NMP in advance was used. The mixture was kneaded with a rotation-revolution type mixer (ARE-310 manufactured by Thinky Corporation) to prepare a positive electrode mixture paste. NMP was added to adjust the total mass of the positive electrode active material, binder, and conductive material in the positive electrode mixture paste to 50% by mass.

[0159] A 20-μm-thick aluminum foil 1085 (manufactured by Nippon Foil Co., Ltd.) for use as a positive electrode current collector for lithium-ion secondary batteries was attached to one side of the foil in an amount of 3.0 ± 0.1 mg / cm2. 2 The positive electrode composite paste was applied so that the positive electrode was formed as follows: After that, it was vacuum dried at 150°C for 8 hours to obtain a positive electrode. The electrode area of ​​this positive electrode was 1.65 cm 2 It was decided.

[0160] <Battery manufacturing> The coin-type battery described below was produced by the following procedure. The above-mentioned positive electrode, electrolyte, separator, and negative electrode were combined to produce a nonaqueous electrolyte secondary battery (coin-type battery). The battery was assembled in a glove box in an argon atmosphere. As the electrolyte, a solution in which LiPF6 was dissolved at a ratio of 1.0 mol / L in a 30:35:35 (volume ratio) mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate was used. As the separator, a laminated film separator in which a heat-resistant porous layer was laminated on a porous film (made of polyethylene) was used, and metallic lithium was used as the negative electrode.

[0161] <Production of positive electrodes before recycling> The positive electrode active material is Li 1.07 Ni 0.47 Mn 0.48 Fe 0.05A positive electrode active material having a crystal structure of R-3m and a molecular weight of 02 was prepared. The above-mentioned coin-type battery was produced using this positive electrode active material (unused positive electrode active material), and the following charge-discharge test (rate test) was carried out while maintaining the temperature at 25°C. The 0.2C discharge capacity was 138mAh / g, and the 5C discharge capacity was 106mAh / g. The larger the 0.2C discharge capacity, the higher the rated capacity obtained, and the larger the 5C discharge capacity, the higher the output characteristics obtained. (conditions) Maximum charging voltage: 4.3V Charging current: 0.2mA / cm 2 Charging time: 8 hours Minimum discharge voltage: 2.5V 0.2C discharge current: 0.2mA / cm 2 5C discharge current: 5.0mA / cm 2

[0162] The electrode mixture was mechanically scraped off from the positive electrode used in the above battery, and the electrode mixture was peeled off from the current collector. 5 g of the electrode mixture removed from the positive electrode was mixed with 0.1 mol of K2CO3 per 1 mol of positive electrode active material and 0.1 mol of Na2CO3 per 1 mol of positive electrode active material as an activation treatment agent to obtain a mixture (mixture before heating). The melting start temperature of the activation treatment agent was 700°C.

[0163] The mixture before heating was placed in an electric furnace and heated in an air atmosphere under conditions of a heating temperature of 700° C. (above the melting start temperature of the activation treatment agent) and a heating time of 240 minutes.

[0164] The mixture after heating was pulverized, and distilled water was added and stirred to obtain a slurry. The obtained slurry was filtered to separate a solid component and a liquid component. The solid component was then collected and dried to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and a charge / discharge test was performed under the above conditions while maintaining the temperature at 25°C. The 0.2C discharge capacity was 135mAh / g, and the 5C discharge capacity was 94mAh / g, which was comparable to the discharge capacity of a coin-type battery produced using an unused positive electrode active material.

[0165] (Reference example 2) <Production of positive electrodes before recycling> The positive electrode active material has the composition LiNi 0.33 Co 0.33 Mn 0.33 A positive electrode active material NCM111 having a crystal structure of R-3m was prepared. When the above coin-type battery was produced using this positive electrode active material (unused positive electrode active material), the initial charge capacity was 178.3mAh / g and the initial discharge capacity (0.2C) was 163.4mAh / g. In addition, when the following charge / discharge test (rate test) was performed while maintaining the temperature at 25°C, the 0.2C discharge capacity was 163.1mAh / g and the 5C discharge capacity was 141.3mAh / g.

[0166] The electrode mixture was mechanically scraped off from the cathode of the process waste material generated during the preparation of the above cathode, and the electrode mixture was peeled off from the current collector. 5 g of the electrode mixture removed from the cathode was mixed with 0.1 mol of Li2CO3 per 1 mol of the cathode active material and 0.1 mol of Na2SO4 per 1 mol of the cathode active material as activation treatment agents to obtain a mixture (mixture before heating). The melting start temperature of the activation treatment agent was 510°C.

[0167] 30 g of the mixture before heating was placed in an electric furnace and heated in an air atmosphere at a heating rate of 300° C. / h, a heating temperature of 450° C. (lower than the melting start temperature of the activation treatment agent), and a heating time of 360 minutes.

[0168] The mixture after heating was pulverized, and distilled water was added and stirred to obtain a slurry. The obtained slurry was filtered to separate a solid component and a liquid component. The solid component was then collected and dried by suction at 100°C for 1 hour.

[0169] The solid component after drying was placed in an electric furnace, and heated in an air atmosphere at a heating temperature of 900°C for 60 minutes to obtain a recycled positive electrode active material after heating. Next, the recycled positive electrode active material after heating was naturally cooled to room temperature, and it was confirmed that the composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. When the above coin-type battery was produced using the recycled positive electrode active material, the initial charge capacity was 180.5mAh / g and the initial discharge capacity was 161.1mAh / g. In addition, when the initial charge / discharge (rate test) was performed under the above conditions while maintaining at 25°C, the 0.2C discharge capacity was 160.2mAh / g and the 5C discharge capacity was 133.9mAh / g.

Claims

1. (1) A step of mixing a positive electrode active material powder and a positive electrode mixture containing a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture; (2) heating the mixture to obtain a heated mixture containing a heated positive electrode active material powder; and (3) A method for producing a recycled positive electrode active material powder, comprising: removing components other than the heated positive electrode active material powder from the heated mixture, Step (3) is (A1) a sub-step of contacting the heated mixture or a partially removed mixture in which components other than the heated positive electrode active material powder are partially removed from the heated mixture with a liquid containing water to obtain a slurry S1 containing the heated positive electrode active material powder; (A2) a sub-step of wet-classifying the heated positive electrode active material powder in the slurry S1 to obtain a slurry S2 containing the heated positive electrode active material powder having a relatively small average particle size and a slurry S3 containing the heated positive electrode active material powder having a relatively large average particle size; and (A3) A sub-step of performing solid-liquid separation of the slurry S3.

2. The method according to claim 1 , wherein the sub-step (A1) is a sub-step of contacting the heated mixture with a liquid containing water to obtain a slurry S1 containing the heated positive electrode active material powder.

3. 2. The method according to claim 1, wherein the sub-step (A1) is a sub-step of contacting a liquid containing water with a partially removed mixture in which components other than the heated positive electrode active material powder have been partially removed from the heated mixture, to obtain a slurry S1 containing the heated positive electrode active material powder.

4. The method according to claim 1 or 2, wherein the wet classification in substep (A2) is carried out using a wet sieve or a wet cyclone.

Citation Information

Patent Citations

  • Method for recovering active material from discarded battery material

    JP2012186150A

  • Valuables sorting method

    JP2022182724A

  • Recovery method of valuables from lithium ion secondary battery

    JP2024010918A

  • Method for producing positive electrode active material

    WO2024048590A1